Manusia dan Islam (Kuala Lumpur Dewan Bahasa dan Pustaka, Kementerian Pendidikan Malaysia, 1990)
Islam and its social aspects, with reference to Malaysia.
In Malay.
Includes bibliographical references and index.and index.
Keywords: Islam